Antagonistic regulation of apoptosis and differentiation by the cut transcription factor represents a tumor-suppressing mechanism in Drosophila - Zhai, Zongzhao; Ha, Nati; Papagiannouli, Fani; Sorge, Sebastian; Lohmann, Ingrid (PLoS Genetics, 2012)
Author Summary Apoptosis is a highly conserved cellular function to remove excessive or unstable cells in diverse developmental processes and disease-responses. An important example is the elimination of cells unable to differentiate, which have the potential to generate tumors. Despite the significance of this process, the mechanisms coupling loss of differentiation and apoptosis have remained elusive. Using cell-type specification in Drosophila as a model, we now identify a conserved regulatory logic that underlies cell-type specific removal of uncommitted cells by apoptosis. We find that the transcription factor Cut activates differentiation, while it simultaneously represses cell death via the direct regulation of a pro-apoptotic gene. We show that this regulatory interaction occurs in many diverse cell types and is essential for normal development. Using in vivo Drosophila cancer models, we demonstrate that apoptosis activation in differentiation-compromised cells is an immediate-early cancer prevention mechanism. Importantly, we show that this type of regulatory wiring is also found in vertebrates and that other cell-type specification factors might employ a similar mechanism for tumor suppression. Thus, our findings suggest that the coupling of differentiation and apoptosis by individual transcription factors is a widely used and evolutionarily conserved cancer prevention module, which is hard-wired into the developmental program.
Gesehen am 24.08.2017